Durability Characteristics of Ceramic Waste based Light Weight Concrete - S, Madhumitha.; G, Dhinakaran. (International Journal of Engineering and Technology, 2018)
Ceramic waste powder (CWP) is one waste material produced during cutting of ceramic tiles. CWP is rich in silica and alumina and is a fine material. Due to generation of more such waste it is mandatory to make use such material effectively in construction industry to minimize the disposal problem and also to reduce production of cement. Use of such material will minimize the carbon foot print in production stage of concrete. LECA is a light weight expanded clay aggregate could be used as substitute to natural coarse aggregate which is energy intensive. In this study, CWP is partially substituted for cement and LECA is partially substituted for natural coarse aggregate. CWP was used from 10 to 30% and LECA was used from 20 to 40%. All the mix combinations were subjected to durability studies namely sorptivity and porosity to study the effectiveness of enhancement on the performance of admixed light weight concrete. All the tests are performed as per ASTM standards. The durability performance of admixed concrete with ceramic waste and LECA aggregate are compared with results of conventional concrete.Â Â